2013
DOI: 10.7883/yoken.66.439
|View full text |Cite
|
Sign up to set email alerts
|

The First Report on the Outbreak of OXA-24/40-Like Carbapenemase-Producing <i>Acinetobacter baumannii</i> in Turkey

Abstract: Carbapenem resistance due to OXA-type carbapenemases seriously limits therapeutic options in nosocomial infections caused by Acinetobacter baumannii. Previous studies have shown the presence of OXA-51, OXA-58, and OXA-23 carbapenemases but not OXA-24/40 in A. baumannii in Turkey. In this study, we investigated carbapenem-hydrolyzing class D b-lactamases (CHDLs) in A. baumannii and the molecular epidemiology of CHDL producers at the Dokuz Eylul Hospital, Izmir Turkey, and detected bla OXA-24/40 in a clinical is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 32 publications
1
5
0
2
Order By: Relevance
“…This agrees with reports of a progressive change from bla OXA-58 to bla OXA-23 carriage worldwide (33). In addition, a recent rise of metallo-β-lactamases in A. baumannii has been observed in some European countries (34,35). However, even though NDM-1 has been detected recently in A. baumannii isolated from Syrian patients hospitalized in Lebanon (18), this metallo-β-lactamase has apparently not diffused to Lebanese patients according to our findings.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This agrees with reports of a progressive change from bla OXA-58 to bla OXA-23 carriage worldwide (33). In addition, a recent rise of metallo-β-lactamases in A. baumannii has been observed in some European countries (34,35). However, even though NDM-1 has been detected recently in A. baumannii isolated from Syrian patients hospitalized in Lebanon (18), this metallo-β-lactamase has apparently not diffused to Lebanese patients according to our findings.…”
Section: Discussionsupporting
confidence: 91%
“…baumannii from close countries like Turkey, where it was responsible for a hospital outbreak in an intensive care ward (34). The OXA-58 oxacillinase, previously reported in a Lebanese hospital (17), was not detected among our isolates.…”
Section: Discussionmentioning
confidence: 42%
“…OXA-51-like, OXA-58-like, OXA-23-like carbapenemase-producing strains were detected widely (3,4). Also, in a recent study, it was reported that a small outbreak was caused by A. baumannii which produced OXA-72, a member of OXA-24/40-like enzymes in a Turkish hospital (5). Four types of MBL enzymes have been identified in A. baumannii isolates including Imipenemase (IMP), Verona Imipenemase (VIM), Seoul Imipenemase (SIM) and New Delhi Metallo betalactamase (NDM)-1-types throughout the World (6).…”
mentioning
confidence: 96%
“…The results of this study supported the proposal that bla OXA-51-like genes are detected in A. baumannii and Acinetobacter nosocomialis strains. The bla OXA-24-like gene was first identified in Izmir in the far western region of Turkey in 2013 [13]. In this study, the rarely identified bla OXA-24-like gene in Turkey and for the first time from Azerbaijan has been reported.…”
Section: Discussionmentioning
confidence: 62%